Dekomposisi Limbah Organik Tempurung Kelapa Menjadi Bio-Coke Hybrid Menggunakan Metode Pirolisis-LSM (Liquid Solid Mixing) - JAHIDING, M (Jounal of Enviromental Science Sustainable, 2024)
Coconut shells (TK) are biomass waste containing lignocellulosic components that have potential as a biomass fuel source. This condition encourages the conversion of TK biomass waste into bio-coke as an alternative solid fuel by combining LVM (Liquid Volatile Matter) into the bio-coke structure to increase the calorific value using the pyrolysis-LSM (Liquid Solid Mixing) method. This research aims to determine the effect of LVM and bio-char CS concentrations as materials for making hybrid bio-coke with LVM concentrations of 10, 20, and 30% (w/t) using pyrolysis at a temperature of 600°. C. The characterization results show that the best proximate and heating values are obtained at an LVM concentration of 30%. Bio-coke hybrid has a water content of 5.12%, ash content of 6%, volatile substances of 20.48%, fixed carbon of 63.38%, and a maximum calorific value of 7186.28 kcal/kg. Thus, LVM combined with TK bio-coke is a potential strategy for managing biomass waste in alternative fuel applications.